The direct-medical costs associated with interferon-based treatment for hepatitis C in Vietnam - Nguyen, HA; Cooke, GS; Day, JN; Flower, B; Phuong, LT; Hung, TM; Dung, NT; Khoa, DB; Hung, LM; Kestelyn, E; Thwaites, GE; Chau, NVV; et al. (F1000Research, 2020)
Background: Injectable interferon-based therapies have been used to treat hepatitis C virus (HCV) infection since 1991. International guidelines have now moved away from interferon-based therapy towards direct-acting antiviral (DAA) tablet regimens, because of their superior efficacy, excellent side-effect profiles, and ease of administration. Initially DAA drugs were prohibitively expensive for most healthcare systems. Access is now improving through the procurement of low-cost, generic DAAs acquired through voluntary licenses. However, HCV treatment costs vary widely, and many countries are struggling with DAA treatment scale-up. This is not helped by the limited cost data and economic evaluations from low- and middle-income countries to support HCV policy decisions. We conducted a detailed analysis of the costs of treating chronic HCV infection with interferon-based therapy in Vietnam. Understanding these costs is important for performing necessary economic evaluations of novel treatment strategies.